Thirty year Africa Diary for 2024: Ten African countries, plus Rwanda - Nicol, Martin; Nicol, Martin (as editor) (New Agenda: South African Journal of Social and Economic Policy, 2024)
New Agenda Number 93 (June 2024) focuses on South Africa and its 30 years of Democracy – but there is a need to recognize Africa beyond the normal 3-month ‘diary of events’. While South Africa has been trying to find the way to make democracy work to address the key national challenges of unemployment and inequality, other countries in Africa have often fared worse. We look at the ten African countries with the highest populations – and Rwanda – to provide a comparative perspective